Allergic Bronchopulmonary Aspergillosis in Bronchial Asthma Children: A Prevalence Study - Sira, Prabhpreet K.; Goindi, Achal S.; Sangha, Jagroop S. (Journal of Advances in Medicine and Medical Research, 2025)
Aim: The aim of this study was to examine the prevalence of allergic bronchopulmonary aspergillosis (ABPA) in children with bronchial asthma. Methods: The study included 200 children with bronchial asthma. We diagnosed ABPA using Aspergillus skin test, pulmonary function test, Absolute Eosinophil count, Total Serum IgE, Aspergillus specific IgE and IgG, Chest Radiograph and high resolution computed tomography. Patients were diagnosed and classified according to Rosenberg-Patterson criteria for ABPA. Results: Of 200 children with bronchial asthma, 7 patients were ABPA positive. 5 (71.4%) cases had uncontrolled asthma amongst ABPA positive cases. Mean AEC was significantly higher in ABPA positive cases (418.71±90.12 cells/cumm). Mean Total serum IgE in the positive cases was 1181.00±403.42 IU/L. The mean A. specific IgE in the positive cases was 4.74±6.09 kUA/l. In the ABPA positive cases, mean A. specific IgG was 26.06±14.93 mgA/L. Conclusion: This study showed an association between ABPA and bronchial asthma in children. ABPA is a common entity in bronchial asthma and should be considered as a cause of uncontrolled asthma, where asthma is poorly controlled despite the use of many medications.